Effect of retained austenite on impact toughness and fracture behavior of medium carbon submicron-structured bainitic steel - S.B. Zhou; F. Hu; W. Zhou; L. Cheng; C.Y. Hu; K.M. Wu (Journal of Materials Research and Technology, 2021)
The effects of retained austenite on the crack propagation behavior of a submicron-structured bainitic steel under impact fracture were studied. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and electron back-scattering diffraction (EBSD) were employed to characterize the size, distribution, and quantity of the matrix structure, and the microstructure of the impact fracture samples under conditions of two different bainitic processes. The retained austenite content at 280 °C was higher than that at 320 °C, and the microstructure appeared more uniform and refined, resulting in better impact toughness. The martensite + retained austenite constituents took part in the initiation of the fracture process and the crack ended at film of retained austenite. During fracture, a mixture of brittle, hard block martensite + retained austenite was easy to induced a crack opening. The effect of the transformation-induced plasticity of the retained austenite with a small block and film can effectively cause passivity and even inhibit crack growth.